Winter of Discontent : a Dorothy Martin mystery - Dams, Jeanne M. (Dams, Jeanne M. Dorothy Martin mysteries, 2004)
Dorothy Martin's neighbor and closest friend, Jane Langland, has been having a fling with Bill Fanshawe--or, as much of a fling as two 80-year olds in a small town are allowed. Now there are rumors that Jane and Bill may move in together, and Dorothy needs to know exactly what's happening. What neither woman expects is that Bill is missing, and that within a day his body is going to be discovered in the tunnel under the Sherebury town museum. Why would anyone want to harm a harmless old man, a historian who loves the town and the people who live there? Given his age, and the strange letter found in his hand, Dorothy thinks that whatever happened has its roots in WWII. Everyone, including her husband, retired police office Alan, looks askance, but when another old man is murdered--a man who served at the same RAF base as Bill--no one denies Dorothy's suspicions may be right. Dorothy investigates, knowing that the best Christmas gift she can give her friend Jane is the truth about what happened to Bill. And Jane has a surprise of her own for Dorothy...